Power conservation for electrically assisted rickshaw-vans with pv support, torque sensor paddle and the solar battery charging station - a complete off- grid solution : commissioning of the systems - Munira, Faiza; Halim, Nazia (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.